The history of British birds - Yalden, D. W. (Derek William); Albarella, Umberto (Oxford : Oxford University Press, 2009)
An integration of ornithological and archaeological evidence on the history, composition and balance of the bird fauna of the British Isles, this book provides essential background information for the debate on extinction, conservation and reintroduction.
Series statement from book jacket.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Birds -- Great Britain -- History; Birds -- British Isles -- History; Bird remains (Archaeology) -- Great Britain; Bird remains (Archaeology) -- British Isles; Birds -- Great Britain; Birds -- British Isles